2013
DOI: 10.1098/rsbl.2013.0056
|View full text |Cite
|
Sign up to set email alerts
|

Queen control of a key life-history event in a eusocial insect

Abstract: In eusocial insects, inclusive fitness theory predicts potential queen-worker conflict over the timing of events in colony life history. Whether queens or workers control the timing of these events is poorly understood. In the bumble-bee Bombus terrestris, queens exhibit a 'switch point' in which they switch from laying diploid eggs yielding females (workers and new queens) to laying haploid eggs yielding males. By rearing foundress queens whose worker offspring were removed as pupae and sexing their eggs usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…A recent study in bumblebees demonstrated that queens have considerable control over their reproduction, and therefore they appear to have retained some plasticity resembling that which is seen in solitary insects, and is also seen in foundresses [41]. Caste differentiation is also more profound in bumblebees compared with Polistes.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study in bumblebees demonstrated that queens have considerable control over their reproduction, and therefore they appear to have retained some plasticity resembling that which is seen in solitary insects, and is also seen in foundresses [41]. Caste differentiation is also more profound in bumblebees compared with Polistes.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, the underlying mechanism behind the timing of the switch from the ergonomic to the reproductive phase is not known (but it has been shown that Bombus terrestris queens are able to control the switching time endogenously, Holland et al. ). Nevertheless, the framework of our model can be used to also study the evolution of eusociality, when we allow for the brood to have control over their own developmental fate.…”
Section: Discussionmentioning
confidence: 99%
“…Inherently, our model assumes that individuals in the colony possess some physiological mechanism that enables them to estimate the timing of the switch from the ergonomic phase to the reproductive phase. Currently, the underlying mechanism behind the timing of the switch from the ergonomic to the reproductive phase is not known (but it has been shown that Bombus terrestris queens are able to control the switching time endogenously, Holland et al 2013). Nevertheless, the framework of our model can be used to also study the evolution of eusociality, when we allow for the brood to have control over their own developmental fate.…”
Section: Colony Growth?mentioning
confidence: 99%
“…Such an approach is important because, in eusocial systems, the colony itself exhibits life‐history characteristics such as growth, reproduction and decline (Wilson ; Starr ; Hou et al . ; Holland, Guidat & Bourke ). In turn, this means that environmental factors, such as temperature, could have effects on colonies different from those occurring in individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, no study has investigated the direct effects of temperature on life-history variables in eusocial bees at both individual and colony levels. Such an approach is important because, in eusocial systems, the colony itself exhibits life-history characteristics such as growth, reproduction and decline (Wilson 1985;Starr 2006;Hou et al 2010;Holland, Guidat & Bourke 2013). In turn, this means that environmental factors, such as temperature, could have effects on colonies different from those occurring in individuals.…”
Section: Introductionmentioning
confidence: 99%